NUTRITIONAL ASSESSMENT OF PANICUM MAXIMUM (JACQ.) ENSILED WITH TWO CULTIVARS OF LABLAB PURPUREUS (LABLAB PURPUREUS L.) FOR WEST AFRICAN DWARF RAM (2014)
Panicum maximum, a grass which is low in Crude Protein (CP), high in fibre and scarce in dry periods. Common legumes are used to improve the quality of P. maximum and preserved as hay and silage for dry season feeding. Lablab purpureus is a legume though rich in protein but not commonly used. Information on P. maximum/Lablab purpureus mixtures as silage for West African Dwarf (WAD) ram production is scanty. The nutritive value of intercropping P. maximum with L. purpureus as well as ensiled mixtures of P. maximum and L. purpureus for WAD ram was evaluated. Panicum maximum was intercropped with two cultivars of L. purpureus (Highworth and Rongai) in a completely randomised block design to determine the effect of grass, grass/legume mixtures on CP contents of grass. Sole grass and grass/legume mixtures: 100% P. maximum (Pm-100), 75% P. maximum+25% Highworth (Pm-75/H-25), 50% P. maximum+50% Highworth (Pm-50/H-50), 25% P. maximum+75% Highworth (Pm-25/H-75), 75% P. maximum+25% Rongai (Pm-75/R-25), 50% P. maximum+50% Rongai (Pm-50/R-50) and 25% P. maximum+75% Rongai (Pm-25/R-75) were ensiled. Silage characteristics were determined. Total Gas Volume (TGV), Metabolizable Energy (ME), Organic Matter Digestibility (OMD), Short Chain Fatty Acid (SCFA) and methane of silages were determined using in vitro Fermentation Technique (ivFT). Twenty-one rams were allotted to seven treatments on ensiled grass and grass- legume mixtures in triplicate for 98 days to assess Feed Intake (FI), Body Weight Gain (BWG), Dry Matter Digestibility (DMD), and nitrogen retention. Blood was sampled for haematology and serum parameters. Data were analysed using descriptive statistics and ANOVA at p=0.05 The CP of P. maximum from P. maximum intercropped with Highworth (8.0%) or Rongai (8.1%) was significantly higher than CP of sole P. maximum (6.5%). Colour of silages was olive green with pleasant odour, firm texture, normal temperature (23-25C) and pH range of 4.1-4.5. Least CP value was observed in Pm-100 (9.0%) and highest in Pm-25/H-75 (16.8%). Highest neutral detergent fibre, acid detergent fibre, acid detergent lignin were 56.1%, 39.4% and 9.4% respectively observed for Pm-100.The TGV (24.7-34.0 mL), ME (6.1-7.5 MJ/KgDM), OMD (48.0-57.1%) SCFA (0.53-0.75 mol), and methane (10.0-15.0 mL) varied significantly among treatments. The least FI (573.87g) and BWG (23.81g) occurred in rams fed Pm-100, while the highest FI (715.47g) and BWG (47.62g) was reported for rams fed Pm-25/R-75 and Pm-25/H-75 respectively. Least DMD (40.4%) was obtained for rams fed Pm-75/R-25, while highest (56.9 %) was for rams on Pm-25/R-75 while animals fed Pm-25/R-75 had the highest FI. Nitrogen retention varied such that rams fed Pm-75/H-25 had the least (30.7%) while those fed Pm-25/R-75 had the highest (56.7%). Highest packed cell volume (37.0%) and total protein (6.46g/dL) occurred in Pm-25/H-75, red blood cell (11.60X106L) in Pm-25/R-75, while highest blood urea (29.00mg/dL) was obtained in Pm-100. Intercropping of Panicum maximum with Lablab purpureus cultivars improved crude protein content of the grass. Ensiling Panicum maximum with 75% Highworth or Rongai enhanced feed intake, weight gain and could serve as a good substitute dry season feed for ram.